2005
DOI: 10.1161/circulationaha.104.512079
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Lipoprotein Abnormalities in Prediabetic Subjects in the Insulin Resistance Atherosclerosis Study

Abstract: Background-Subjects with type 2 diabetes have smaller LDL and HDL particles in addition to higher levels of triglycerides and lower HDL cholesterol. Elevated insulin resistance, blood pressure, and dyslipidemia (including small dense LDL) predicted incident diabetes. In the Insulin Resistance Atherosclerosis Study (IRAS) we studied nuclear magnetic resonance (NMR) lipoprotein particle measures in prediabetic individuals, considering potentially modifying covariates, including insulin resistance, as directly me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
182
2
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(199 citation statements)
references
References 37 publications
(34 reference statements)
11
182
2
4
Order By: Relevance
“…Thus, we found that insulin sensitivity was reduced concomitant with reduction of large VLDL and small HDL particle concentrations and also with reduction of VLDL size. Discrepancies between effects on insulin sensitivity and effects on small HDL and VLDL size were also reported by Festa et al (2005). Thus, it seems clear that insulin sensitivity does not exert an overriding influence on particle concentration of large VLDL and small HDL, or on VLDL size.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, we found that insulin sensitivity was reduced concomitant with reduction of large VLDL and small HDL particle concentrations and also with reduction of VLDL size. Discrepancies between effects on insulin sensitivity and effects on small HDL and VLDL size were also reported by Festa et al (2005). Thus, it seems clear that insulin sensitivity does not exert an overriding influence on particle concentration of large VLDL and small HDL, or on VLDL size.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, people with a small mean LDL particle size have relatively more small LDL particles as compared with people with a large mean LDL particle sizes. Small LDL particle sizes are associated with type II diabetes (Festa et al 2005), metabolic syndrome (Gentile et al 2008;Kathiresan et al 2006), insulin resistance (Garvey et al 2003;Goff et al 2005), incident CVD (Mora et al 2009), and future CAD (El Harchaoui et al 2007). Possible atherosclerosis could be induced by those small LDL particles, as indicated in a study of two knockout mice strains with similar cholesterol levels, were the Ldr −/− Apob 100/100 mice had a larger number (Veniant et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…CONCLUSIONS -This study is the first to demonstrate that PIO and ROSI treatments result in significantly different effects on serum lipoprotein subclass particle concentrations and sizes despite similar effects on glycemic control and insulin resistance. These observations were made utilizing NMR spectroscopy, a novel technique that permits evaluation of these important characteristics of lipoproteins, and as such has advanced our understanding of the changes in serum lipoprotein subclass particle concentration and size under normal conditions (16,20), in specific disease states (7, [21][22][23], and during treatment with specific drug therapies (24 -26). Garvey et al (7) reported that all three major lipoprotein subclasses differed significantly as a function of insulin sensitivity in insulin-resistant nondiabetic subjects and type 2 diabetic patients.…”
Section: Hdlmentioning
confidence: 99%